Illuminating Medical Education Through Moral Case Deliberations: A Narrative Review - Saurabh RamBihariLal Shrivastava; Ujwal Gajbe; Brij Raj Singh; Prateek Saurabh Shrivastava; Nandkishor J Bankar; Manju Chandankhede (Wolters Kluwer Medknow Publications, 2024)
In the field of medical education, moral case deliberations refer to a structured process, wherein health professionals together discuss and analyze moral issues or ethical dilemmas encountered in their clinical practice. The purpose of the current review is to explore the merits of moral case deliberations, identify the components, enumerate the strategies that can be used for implementation, and enlist the potential challenges and the remedial measures to overcome them. Moral case deliberations can be implemented in medical education in several ways that can be seamlessly integrated into the existing medical curriculum without stretching the overall duration of the training period. The path to successfully implement moral case deliberations in a medical school has its own share of challenges, and we must be aware of them to adopt countermeasures to overcome them. In conclusion, moral case deliberations play a vital role in augmenting ethical competence and establishing a culture of reflective practice among medical students. As medical students are bound to encounter multiple ethical dilemmas in their future clinical practice, it is our responsibility to incrementally expose them to such cases as a part of their undergraduate training to eventually prepare them for effective healthcare delivery.